Borate modified positive electrode material as well as preparation method and application thereof
By constructing a uniform metal borate coating on the surface of the positive electrode material of the lithium-ion battery, the problem of difficulty in forming a uniform coating in the prior art is solved, and the cycle stability and rate performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202311263393.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-01
AI Technical Summary
The prior art is difficult to form a uniform lithium borate coating on the substrate surface of the positive electrode material of lithium-ion battery, resulting in the inability to fully exert the regulatory and modification effect of borate on the structure and performance of the substrate material.
By dissolving the polyol, metal salt, boric acid and alkali in a solvent, a mixed solution is formed, and the coating substrate material is dispersed in this solution, and a uniform metal borate coating layer is constructed through anti-solvent stirring, centrifugation, washing and calcining.
A uniform borate coating is achieved on the surface of the positive electrode material of the lithium-ion battery, which significantly improves the cycle stability and rate performance of the battery and extends the battery life.
Smart Images

Figure CN119735212A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of chemical materials, and specifically relates to a borate-modified positive electrode material and a preparation method and application thereof. Background Art
[0002] Surface coating refers to the process of introducing heterogeneous species into the surface of a material to form a composite material with a core-shell structure. The newly formed coated material generally has a stable structure and has broad application prospects in catalysis, sensing, drug delivery, energy conversion and other fields. In particular, it plays an important role in stabilizing the interface of positive electrode materials for lithium-ion batteries. By forming a nano-protective layer on the surface of the positive electrode material substrate, the electrode material's own structural degradation and the generation of surface side reactions during the cycle can be significantly improved, the battery's interfacial impedance can be greatly reduced, and rapid lithium ion transmission can be promoted, which has a direct impact on improving the overall cycle stability and rate performance of the battery.
[0003] As a material full of potential, borate can play an excellent stabilizing role at the interface of lithium-ion battery positive electrode materials. At present, the method of borate coating is mainly limited to the traditional simple high-temperature solid phase mixing method, liquid phase impregnation method, etc. In recent years, the invention patent CN114853089A of Chuneng New Energy Co., Ltd. uses solid phase mixing combined with high-temperature sintering to coat magnesium borate on the surface of high-nickel ternary positive electrode materials. A small number of patents such as CN110010865A use solution immersion methods to prepare high-nickel positive electrode materials coated with lithium chloroborate, which all show that the introduction of borate coating is conducive to the improvement of battery cycle performance and rate performance. However, the above-mentioned uncontrolled methods such as direct mixing and immersion cannot form a uniform coating layer of lithium borate on the surface of the positive electrode substrate, and it is impossible to ensure that the borate can maximize the regulation and modification of the structure and performance of the substrate material. Therefore, in order to give full play to the unique advantages of borate coating, it is of great significance to develop a new method that can construct a uniform borate coating layer on the surface of the substrate material. Summary of the invention
[0004] The purpose of the present invention is to provide a borate-modified positive electrode material and a preparation method and application thereof.
[0005] To solve the above problems, the present invention provides the following technical solutions:
[0006] A method for preparing a borate-modified positive electrode material, the preparation method comprising:
[0007] 1) dissolving polyol, metal salt, boric acid and alkali in a solvent, reacting to form a mixed solution;
[0008] 2) dispersing the coated substrate material in the mixed solution formed in step 1) to obtain a turbid solution;
[0009] 3) stirring the anti-solvent and the turbid liquid formed in step 2) to react, centrifuging, washing, and drying to obtain a base powder coated with a metal boric acid precursor species;
[0010] 4) The base powder formed in step 3) is calcined to obtain a borate-coated positive electrode material.
[0011] According to an embodiment of the present invention, the polyol includes but is not limited to one or more of ethylene glycol, glycerol, tetraethylene glycol, mannitol, xylitol, sorbitol, glucose, pentaerythritol, diethylene glycol, dipropylene glycol, triethylene glycol, tetraethylene glycol, hexaethylene glycol, octaethylene glycol, polyethylene glycol 200, polyethylene glycol 400, and polyethylene glycol 600, preferably glycerol, mannitol, and glucose.
[0012] According to an embodiment of the present invention, in the mixed solution of step 1), the concentration of the polyol is 0.001 to 1 mol / L.
[0013] According to an embodiment of the present invention, the metal salt is selected from one or more of chlorides, sulfates, nitrates, acetates and alkoxides of metal elements, preferably metal chlorides and metal nitrates. Preferably, the metal element is selected from at least one of yttrium, lanthanum, cerium, praseodymium, neodymium, ytterbium, holmium, gadolinium, lutetium, scandium, titanium, niobium, tantalum, zirconium, aluminum, magnesium, hafnium, manganese, cobalt, iron, nickel and copper, preferably yttrium and ytterbium.
[0014] According to an embodiment of the present invention, in the mixed solution of step 1), the concentration of the metal salt is 0.001 to 1 mol / L.
[0015] According to an embodiment of the present invention, the base includes but is not limited to one or more of lithium hydroxide, potassium hydroxide, sodium hydroxide, and ammonia water, preferably lithium hydroxide.
[0016] According to an embodiment of the present invention, in the mixed solution of step 1), the alkali concentration is 0.001 to 1 mol / L.
[0017] According to an embodiment of the present invention, the solvent includes but is not limited to one or more of methanol, ethanol, propanol, isopropanol, butanol, pentanol, and hexanol, preferably methanol and ethanol.
[0018] According to an embodiment of the present invention, in the mixed solution of step 1), the reaction conditions for forming the mixed solution include: the reaction temperature is room temperature to 60°C, preferably room temperature; the reaction time for forming the mixed solution is 1h-72h, preferably 4-10h.
[0019] According to an embodiment of the present invention, in the mixed solution of step 1), the molar ratio of the polyol, the metal salt and the base is 0.001-1:0.001-1:0.001-1.
[0020] According to an embodiment of the present invention, in the mixed solution of step 1), the molar ratio of the boric acid to the metal salt is 0.001-1:0.001-1, for example, 0.006:0.002.
[0021] According to an embodiment of the present invention, the coating substrate material is selected from at least one of metal materials, non-metal materials, oxides, sulfides, carbides, nitrides, phosphides, lithium salt positive electrode materials, sodium salt positive electrode materials, potassium salt positive electrode materials, and organic particles.
[0022] According to an embodiment of the present invention, the metal in the coating substrate material is selected from at least one of gold, silver, ruthenium, rhodium, palladium, platinum, germanium, tin, antimony and alloys thereof.
[0023] According to an embodiment of the present invention, the non-metal in the coating substrate material is selected from at least one of carbon, silicon, sulfur, phosphorus and selenium.
[0024] According to an embodiment of the present invention, the oxide in the coated substrate material is selected from at least one of silicon dioxide, titanium dioxide, aluminum oxide, zinc oxide, magnesium oxide, calcium oxide, manganese dioxide, manganese tetraoxide, iron oxide, iron oxide, cobalt oxide, nickel oxide, vanadium pentoxide, zirconium oxide, molybdenum oxide, indium tin oxide, tin oxide, and lithium lanthanum zirconium oxide.
[0025] According to an embodiment of the present invention, the sulfide in the coated substrate material is selected from at least one of zinc sulfide, tungsten sulfide, bismuth sulfide, titanium disulfide, iron sulfide, cobalt sulfide, nickel sulfide, molybdenum sulfide, tin sulfide and antimony sulfide.
[0026] According to an embodiment of the present invention, the carbide in the coating substrate material is selected from at least one of silicon carbide, titanium carbide, calcium carbide, vanadium carbide, chromium carbide, tantalum carbide, tungsten carbide and boron carbide.
[0027] According to an embodiment of the present invention, the nitride in the coating substrate material is selected from at least one of boron nitride, gallium nitride, silicon nitride, titanium nitride, vanadium nitride, niobium nitride, tungsten nitride and phosphorus nitride.
[0028] According to an embodiment of the present invention, the phosphide in the coated substrate material is selected from at least one of iron phosphide, cobalt phosphide, nickel phosphide, titanium phosphide, molybdenum phosphide and tin phosphide.
[0029] According to an embodiment of the present invention, the lithium salt positive electrode material in the coated substrate material includes but is not limited to at least one of lithium titanate, lithium cobaltate, lithium nickelate, lithium manganate, lithium nickel manganate, lithium nickel cobalt manganate, lithium nickel cobalt aluminum oxide, lithium-rich nickel cobalt manganese oxide, lithium titanium phosphate, lithium titanium aluminum phosphate, lithium vanadium phosphate, lithium iron phosphate, lithium manganese phosphate, lithium cobalt phosphate, lithium iron manganese phosphate, and lithium manganese cobalt phosphate.
[0030] According to an embodiment of the present invention, the sodium salt positive electrode material in the coated substrate material includes but is not limited to at least one of oxide sodium salt positive electrode materials, polyanion sodium salt positive electrode materials, Prussian blue sodium salt positive electrode materials, fluoride sodium salt positive electrode materials, and organic compound sodium salt positive electrode materials.
[0031] According to an embodiment of the present invention, the potassium salt positive electrode material in the coated substrate material includes but is not limited to at least one of Prussian blue-based potassium salt positive electrode materials, layered oxide-based potassium salt positive electrode materials, polyanion-based potassium salt positive electrode materials, and organic material-based potassium salt positive electrode materials.
[0032] According to an embodiment of the present invention, the organic particles in the coating substrate material are selected from at least one of phenolic resin, urea-formaldehyde resin, melamine resin, polystyrene, polydopamine, and polyvinyl pyrrolidone.
[0033] According to an embodiment of the present invention, in step 2), the turbid liquid is further obtained by ultrasonic dispersion and / or stirring.
[0034] According to an embodiment of the present invention, in the turbid liquid of step 2), the concentration of the coating substrate material is 0.001 to 1000 g / L.
[0035] According to an embodiment of the present invention, the anti-solvent includes but is not limited to at least one of methyl ethyl ketone, acetone, butanone, methyl isobutyl ketone, cyclohexanone, isophorone, furfural, acetonitrile, ethyl acetate, and dioxane, preferably acetone.
[0036] According to an embodiment of the present invention, in step 3), the volume ratio of the turbid liquid to the anti-solvent is 1-30:20-50, for example, 15:30.
[0037] According to an embodiment of the present invention, in step 3), the method of mixing the turbid liquid with the anti-solvent comprises: directly pouring the turbid liquid, slowly dripping it, or controlling the dripping rate by a peristaltic pump to drip into the anti-solvent, or directly pouring the anti-solvent, slowly dripping it, or controlling the dripping rate by a peristaltic pump to drip into the turbid liquid.
[0038] According to an embodiment of the present invention, in step 3), the stirring condition is: the stirring temperature is room temperature to 50° C., preferably room temperature.
[0039] According to an embodiment of the present invention, in step 3), the rotation speed of high-speed stirring is between 100 r / min and 1000 r / min, preferably 600 r / min.
[0040] According to an embodiment of the present invention, in step 3), the reaction time is 5 to 300 minutes.
[0041] According to an embodiment of the present invention, in step 4), the calcination atmosphere is at least one of oxygen, air, nitrogen and argon.
[0042] According to an embodiment of the present invention, in step 4), the calcination conditions include: a calcination temperature of 300 to 900° C. and a calcination time of 1 to 10 h.
[0043] The present invention also provides a borate-modified positive electrode material, and the borate-modified positive electrode material is prepared by the above-mentioned preparation method.
[0044] According to an embodiment of the present invention, the borate-modified positive electrode material is a particle having a core-shell structure.
[0045] According to an embodiment of the present invention, the borate-modified positive electrode material comprises a nano-coating shell layer and a coating substrate material, wherein the nano-coating shell layer is modified on the surface of the coating substrate material; the coating substrate material has the meaning as described above; and the nano-coating shell layer comprises a borate. Preferably, the nano-coating shell layer partially coats or fully coats the surface of the coating substrate material, preferably fully coats. Further, the nano-coating shell layer is continuously and evenly distributed on the surface of the coating substrate material.
[0046] According to an embodiment of the present invention, the nano-coating shell layer includes borates of metal elements, such as but not limited to yttrium borate, lanthanum borate, cerium borate, praseodymium borate, neodymium borate, ytterbium borate, holmium borate, gadolinium borate, lutetium borate, scandium borate, titanium borate, niobium borate, tantalum borate, zirconium borate, aluminum borate, magnesium borate, hafnium borate, manganese borate, cobalt borate, iron borate, nickel borate, and copper borate, preferably yttrium borate and lanthanum borate.
[0047] According to an embodiment of the present invention, the thickness of the nano-coating shell layer is 0 nm to 500 nm, for example, 1 nm, 1.5 nm, 5 nm, 10 nm, 50 nm, 100 nm, 200 nm, 300 nm, or 400 nm.
[0048] The present invention also provides application of the borate-modified positive electrode material in energy storage batteries.
[0049] Specifically, it is used to construct high-energy-density energy storage batteries with high cycle stability and long life.
[0050] Beneficial effects:
[0051] The method of the present invention can be used as a new strategy for constructing a borate modified coating layer on the surface of a positive electrode material of a lithium ion battery or a lithium battery.
[0052] The obtained metal borate coated particles with a core-shell structure can be used as a base material for controllably and uniformly coating the positive electrode material of a lithium ion battery or a lithium battery.
[0053] The metal borate-modified positive electrode material particles obtained by the present invention can be used as positive electrodes of high-energy-density lithium-ion batteries or lithium batteries with high cycle stability and long life.
[0054] The present invention provides a surface borate-modified positive electrode material and a preparation method and application thereof, wherein a polyol, boric acid, and metal salt are fully chemically reacted under the action of an alkali, and then an anti-solvent interacts with the polyol, and a uniform layer of metal boron-containing precursor species is controllably grown and deposited on the surface of a pre-added substrate material, that is, particles with a core-shell structure having a metal boron-containing species as a shell and a substrate material as a core are formed. The thickness of the coating layer of the surface metal boron-containing species can be conveniently controlled by changing the mixing mode between solvents, the content of the substrate material, the reaction temperature, and regulating the concentration of the metal salt, boric acid, polyol, and alkali. The present invention provides a convenient, mild, and controllable liquid phase method, which ensures the coating of the metal borate on the surface of the substrate material, and has very important applications for stabilizing the interface of lithium-ion batteries or lithium batteries.
[0055] This invention provides a method for constructing a borate coating layer by controlling a liquid phase reaction. The method utilizes the coordination reaction between a polyol, a metal salt, and boric acid, and deposits a uniform and continuous layer of metal borate precursor species on the surface of a substrate material through the interaction between a precursor solvent and an antisolvent, and converts it into a borate-coated substrate material by heat treatment. This mild, convenient, and controllable coating method is suitable for the construction of different substrate materials and different metal borate shell structures. The borate-modified lithium-ion battery positive electrode particles formed in this way have a more stable interface structure and exhibit enhanced electrochemical cycle stability and rate performance.
[0056] The present invention uses a liquid phase control method to introduce a uniform borate nanoshell layer on the surface of the positive electrode material of a lithium-ion battery. The control strategy is not only conducive to effectively isolating the side reactions between the highly active positive electrode surface and the organic electrolyte during the cycle, and reducing the interface impedance of the interface battery; at the same time, the thickness of the borate nanoshell layer is convenient and adjustable, which is conducive to stabilizing the interface structure without losing the capacity of the battery, and promoting the conduction of lithium ions at the interface. This uniform borate modification strategy can maximize the effect of surface borates on improving the comprehensive electrochemical performance, and is of great value for studying the structure-activity relationship of surface borate modification on the structure and performance regulation of lithium-ion battery positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 This is a transmission electron microscope photograph of the yttrium borate-coated silica nanoparticles of Example 1.
[0058] Figure 2 This is a transmission electron microscope photograph of the yttrium borate-coated silica nanoparticles of Example 1 at a magnified multiple.
[0059] Figure 3 This is a transmission electron microscope photograph of the 20nm yttrium borate-coated high-nickel single crystal lithium nickel cobalt manganese oxide of Example 2.
[0060] Figure 4 This is a transmission electron microscope photograph of the 12nm yttrium borate-coated high-nickel single crystal lithium nickel cobalt manganese oxide of Example 3.
[0061] Figure 5 This is a transmission electron microscope photograph of the 6nm yttrium borate-coated high single crystal nickel nickel cobalt lithium manganese oxide of Example 4.
[0062] Figure 6 The cycle performance of the positive electrode materials corresponding to Example 4 and Comparative Examples 1 and 2 at a charge and discharge current of 200 mA / g. DETAILED DESCRIPTION
[0063] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0064] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0065] Example 1
[0066] Preparation of Yttrium Borate-Modified Nano-Silica Particles with Core-Shell Structure
[0067] 1) Dissolve 0.124 g of boric acid, 0.184 g of glycerol, 0.27 g of yttrium nitrate hexahydrate, and 0.085 g of lithium hydroxide in 15 ml of methanol in sequence, stir and dissolve continuously, and react for 6 hours to form a mixed solution B;
[0068] 2) dispersing 0.1 g of nano-silicon dioxide substrate material in the mixed solution B formed in step 1), ultrasonically dispersing and stirring to obtain a turbid solution;
[0069] 3) 30 ml of acetone and the turbid solution formed in step 2) were reacted at 600 r / min for 1 hour, and the substrate powder coated with the yttrium borate precursor species was obtained after centrifugation, washing and drying;
[0070] 4) The base powder formed in step 3) is calcined at high temperature to obtain nano-silicon dioxide particles modified with yttrium borate.
[0071] The nano-silica particles modified with yttrium borate have a typical core-shell structure, as shown in the transmission electron microscope photo. Figure 1 The average size of the base silica particles is about 400-500nm, and the surface shell thickness is 32nm, as shown in the transmission electron microscope photo at magnification. Figure 2 As shown, yttrium borate is continuously and evenly distributed on the surface of silica nanoparticles.
[0072] Example 2
[0073] Preparation of 20 nm yttrium borate-modified high-nickel single-crystalline lithium nickel cobalt manganese oxide particles with core-shell structure
[0074] 1) Dissolve 0.124 g of boric acid, 0.184 g of glycerol, 0.27 g of yttrium nitrate hexahydrate, and 0.085 g of lithium hydroxide in 15 ml of methanol in sequence, stir and dissolve continuously, and react for 6 hours to form a mixed solution B;
[0075] 2) dispersing 2.1 g of high-nickel single crystal nickel cobalt manganese oxide particles in the mixed solution B formed in step 1), ultrasonically dispersing and stirring to obtain a turbid solution;
[0076] 3) 30 ml of acetone and the turbid solution formed in step 2) were reacted at 600 r / min for 1 hour, and the substrate powder coated with the yttrium borate precursor species was obtained after centrifugation, washing and drying;
[0077] 4) The base powder formed in step 3) is calcined at high temperature to obtain lithium nickel cobalt manganese oxide particles modified with yttrium borate.
[0078] The high-nickel single-crystal nickel cobalt manganese oxide particles modified by yttrium borate are typical core-shell structures, as shown in the transmission electron microscope photo. Figure 3The average size of the substrate lithium nickel cobalt manganese oxide particles is about 1-10 μm, the thickness of the surface shell is 20 nm, and yttrium borate is continuously and evenly distributed on the surface of the lithium nickel cobalt manganese oxide particles.
[0079] Example 3
[0080] Preparation of 12nm yttrium borate-modified high-nickel single-crystalline lithium nickel cobalt manganese oxide particles with core-shell structure
[0081] 1) Dissolve 0.062g of boric acid, 0.092g of glycerol, 0.135g of yttrium nitrate hexahydrate, and 0.042g of lithium hydroxide in 15ml of methanol, stir and dissolve continuously, and react for 6h to form a mixed solution B;
[0082] 2) dispersing 2.1 g of high-nickel single crystal nickel cobalt manganese oxide particles in the mixed solution B formed in step 1), ultrasonically dispersing and stirring to obtain a turbid solution;
[0083] 3) 30 ml of acetone and the turbid solution formed in step 2) were reacted at 600 r / min for 1 hour, and the substrate powder coated with the yttrium borate precursor species was obtained after centrifugation, washing and drying;
[0084] 4) The base powder formed in step 3) is calcined at high temperature to obtain lithium nickel cobalt manganese oxide particles modified with yttrium borate.
[0085] The high-nickel single-crystal nickel cobalt manganese oxide particles modified by yttrium borate are typical core-shell structures, as shown in the transmission electron microscope photo. Figure 4 The average size of the substrate lithium nickel cobalt manganese oxide particles is about 1-10 μm, the thickness of the surface shell is 12 nm, and yttrium borate is continuously and evenly distributed on the surface of the lithium nickel cobalt manganese oxide particles.
[0086] Example 4
[0087] 1. Preparation of 6nm yttrium borate-modified high-nickel single-crystalline lithium nickel cobalt manganese oxide particles with core-shell structure
[0088] 1) Dissolve 0.062 g of boric acid, 0.092 g of glycerol, 0.135 g of yttrium nitrate hexahydrate, and 0.042 g of lithium hydroxide in 15 ml of methanol in sequence, stir and dissolve continuously, and react for 6 hours to form a mixed solution B;
[0089] 2) dispersing 4 g of high-nickel single crystal nickel cobalt manganese oxide particles in the mixed solution B formed in step 1), ultrasonically dispersing and stirring to obtain a turbid solution;
[0090] 3) 30 ml of acetone and the turbid solution formed in step 2) were reacted at 600 r / min for 1 hour, and the substrate powder coated with the yttrium borate precursor species was obtained after centrifugation, washing and drying;
[0091] 4) The base powder formed in step 3) is calcined at high temperature to obtain lithium nickel cobalt manganese oxide particles modified with yttrium borate.
[0092] The high-nickel single-crystal nickel-cobalt-manganese oxide particles modified by yttrium borate are typical core-shell structures, as shown in the transmission electron microscope photo. Figure 5 The average size of the substrate lithium nickel cobalt manganese oxide particles is about 1-10 μm, the surface shell thickness is 6 nm, and yttrium borate is continuously and evenly distributed on the surface of the lithium nickel cobalt manganese oxide particles.
[0093] 2. Preparation of single crystal lithium nickel cobalt manganese oxide electrode modified by yttrium borate
[0094] 0.24 g of the modified single crystal nickel cobalt manganese oxide particles in the above Example 4 were mixed with 0.03 g of acetylene black as a conductive additive, 0.6 g of PVDF with a binder concentration of 5% by mass, and a small amount of solvent NMP. After slurrying, coating (aluminum sheet as current collector), and drying, yttrium borate modified nickel cobalt manganese oxide electrode sheets were obtained.
[0095] 3. Assemble the battery
[0096] The single crystal nickel cobalt manganese oxide electrode modified by yttrium borate prepared above was used as the positive electrode, lithium metal was used as the negative electrode, a polypropylene microporous membrane (Celgard 2400) was used as the separator, and 1 mol / L LiPF6 was used as the electrolyte to assemble a button cell in an argon-protected glove box.
[0097] 4. Battery Test
[0098] The above battery was subjected to constant current charge and discharge test using a charge and discharge instrument, with the test voltage range of 3 to 4.5 V and the test temperature of 25° C. The battery specific capacity and charge and discharge current were calculated based on the mass of lithium nickel cobalt manganese oxide.
[0099] Comparative Example 1
[0100] 1. Take the uncoated positive electrode material to prepare an uncoated high-nickel single crystal nickel cobalt manganese oxide electrode, and the specific steps are the same as step 2 in Example 4.
[0101] 2. Assemble the battery. The specific steps are the same as step 3 in embodiment 4.
[0102] 3. Battery test: the specific steps are the same as step 4 in embodiment 4.
[0103] Comparative Example 2
[0104] 1. Preparation of Lithium Nickel Cobalt Manganese Oxide Particles Partially Coated with Yttrium Borate
[0105] 1) Dissolve 0.062 g of boric acid, 0.092 g of glycerol, 0.135 g of yttrium nitrate hexahydrate, and 0.042 g of lithium hydroxide in 15 ml of methanol in sequence, stir and dissolve continuously, and react for 6 hours to form a mixed solution B;
[0106] 2) dispersing 4 g of high-nickel single crystal nickel cobalt manganese oxide particles in the mixed solution B formed in step 1), ultrasonically dispersing and stirring, and centrifuging, washing, and drying the formed turbid solution to obtain a partially coated substrate powder;
[0107] 3) The base powder formed in step 2) is calcined at high temperature to obtain a partially coated nickel cobalt manganese oxide lithium particle positive electrode material.
[0108] 2. Prepare a partially coated high-nickel single crystal nickel cobalt manganese oxide electrode, the specific steps are the same as step 2 in Example 4.
[0109] 3. Assemble the battery. The specific steps are the same as step 3 in Example 4.
[0110] 4. Battery test: the specific steps are the same as step 4 in embodiment 4.
[0111] Figure 6 The cycle performance (voltage range 3-4.5V) of the positive electrode materials corresponding to Example 4 and Comparative Examples 1 and 2 at a charge and discharge current of 1C (200mA / g). In the activation stage, the modified positive electrode material in Example 4 exhibits a discharge specific capacity of up to 211.2mAh / g under 0.2C conditions, which is higher than the 209.6mAh / g of the original sample in Comparative Example 1. In the 1C cycle process, after the battery has been cycled for 100 cycles, the modified sample in Example 4 exhibits a capacity retention rate of 90%, which is significantly higher than the 84% of the uncoated sample in Comparative Example 1 and the 85% of the partially coated sample in Comparative Example 2, which significantly improves the capacity and cycle stability of the battery, reflecting that the uniformly modified interface structure created by this method provides the battery with excellent electrochemical performance.
[0112] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a borate-modified positive electrode material, characterized in that: The preparation method comprises: 1) dissolving polyol, metal salt, boric acid and alkali in a solvent, reacting to form a mixed solution; 2) dispersing the coated substrate material in the mixed solution formed in step 1) to obtain a turbid solution; 3) stirring the anti-solvent and the turbid liquid formed in step 2) to react, centrifuging, washing, and drying to obtain a base powder coated with a metal boric acid precursor species; 4) The base powder formed in step 3) is calcined to obtain a borate-modified positive electrode material.
2. The preparation method according to claim 1, characterized in that: The polyol includes, but is not limited to, one or more of ethylene glycol, glycerol, tetraethylene glycol, mannitol, xylitol, sorbitol, glucose, pentaerythritol, diethylene glycol, dipropylene glycol, triethylene glycol, tetraethylene glycol, hexaethylene glycol, octaethylene glycol, polyethylene glycol 200, polyethylene glycol 400, and polyethylene glycol 600. Preferably, in the mixed solution of step 1), the concentration of the polyol is 0.001 to 1 mol / L. Preferably, the metal salt is selected from one or more of chlorides, sulfates, nitrates, acetates and alkoxides of metal elements. Preferably, the metal element is selected from at least one of yttrium, lanthanum, cerium, praseodymium, neodymium, ytterbium, holmium, gadolinium, lutetium, scandium, titanium, niobium, tantalum, zirconium, aluminum, magnesium, hafnium, manganese, cobalt, iron, nickel and copper.
3. The preparation method according to claim 1 or 2, characterized in that: In the mixed solution of step 1), the concentration of the metal salt is 0.001 to 1 mol / L. Preferably, the base includes but is not limited to one or more of lithium hydroxide, potassium hydroxide, sodium hydroxide, and ammonia water. Preferably, in the mixed solution of step 1), the alkali concentration is 0.001 to 1 mol / L. Preferably, the solvent includes but is not limited to one or more of methanol, ethanol, propanol, isopropanol, butanol, pentanol and hexanol. Preferably, in the mixed solution of step 1), the reaction conditions for forming the mixed solution include: the reaction temperature is room temperature to 60° C.; and the reaction time for forming the mixed solution is 1 h to 72 h. Preferably, in the mixed solution of step 1), the molar ratio of the polyol, the metal salt and the base is 0.001-1:0.001-1:0.001-1. Preferably, in the mixed solution of step 1), the molar ratio of the boric acid to the metal salt is 0.001-1:0.001-1.
4. The preparation method according to any one of claims 1 to 3, characterized in that The coating substrate material is selected from at least one of metal materials, non-metal materials, oxides, sulfides, carbides, nitrides, phosphides, lithium salt positive electrode materials, sodium salt positive electrode materials, potassium salt positive electrode materials, and organic particles. Preferably, the metal in the coating substrate material is selected from at least one of gold, silver, ruthenium, rhodium, palladium, platinum, germanium, tin, antimony and alloys thereof. Preferably, the non-metal in the coating substrate material is selected from at least one of carbon, silicon, sulfur, phosphorus and selenium. Preferably, the oxide in the coating substrate material is selected from at least one of silicon dioxide, titanium dioxide, aluminum oxide, zinc oxide, magnesium oxide, calcium oxide, manganese dioxide, manganese tetraoxide, iron oxide, iron oxide, cobalt oxide, nickel oxide, vanadium pentoxide, zirconium oxide, molybdenum oxide, indium tin oxide, tin oxide, and lithium lanthanum zirconium oxide. Preferably, the sulfide in the coating substrate material is selected from at least one of zinc sulfide, tungsten sulfide, bismuth sulfide, titanium disulfide, iron sulfide, cobalt sulfide, nickel sulfide, molybdenum sulfide, tin sulfide and antimony sulfide. Preferably, the carbide in the coating substrate material is selected from at least one of silicon carbide, titanium carbide, calcium carbide, vanadium carbide, chromium carbide, tantalum carbide, tungsten carbide and boron carbide. Preferably, the nitride in the coating substrate material is selected from at least one of boron nitride, gallium nitride, silicon nitride, titanium nitride, vanadium nitride, niobium nitride, tungsten nitride and phosphorus nitride. Preferably, the phosphide in the coating substrate material is selected from at least one of iron phosphide, cobalt phosphide, nickel phosphide, titanium phosphide, molybdenum phosphide and tin phosphide. Preferably, the lithium salt positive electrode material in the coating substrate material includes but is not limited to at least one of lithium titanate, lithium cobaltate, lithium nickelate, lithium manganate, lithium nickel manganate, lithium nickel cobalt manganate, lithium nickel cobalt aluminum oxide, lithium-rich nickel cobalt manganese oxide, lithium titanium phosphate, lithium titanium aluminum phosphate, lithium vanadium phosphate, lithium iron phosphate, lithium manganese phosphate, lithium cobalt phosphate, lithium iron manganese phosphate, and lithium manganese cobalt phosphate. Preferably, the sodium salt positive electrode material in the coating substrate material is selected from at least one of oxide sodium salt positive electrode materials, polyanion sodium salt positive electrode materials, Prussian blue sodium salt positive electrode materials, fluoride sodium salt positive electrode materials, and organic compound sodium salt positive electrode materials. Preferably, the potassium salt positive electrode material in the coating substrate material is selected from at least one of Prussian blue-based potassium salt positive electrode materials, layered oxide-based potassium salt positive electrode materials, polyanion-based potassium salt positive electrode materials, and organic material-based potassium salt positive electrode materials. Preferably, the organic particles in the coating substrate material are selected from at least one of phenolic resin, urea-formaldehyde resin, melamine resin, polystyrene, polydopamine and polyvinyl pyrrolidone.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In the turbid liquid of step 2), the concentration of the coated substrate material is 0.001-1000 g / L. Preferably, the anti-solvent includes but is not limited to at least one of methyl ethyl ketone, acetone, butanone, methyl isobutyl ketone, cyclohexanone, isophorone, furfural, acetonitrile, ethyl acetate and dioxane. Preferably, in step 3), the volume ratio of the turbid liquid to the anti-solvent is 1-30:20-50. Preferably, in step 3), the method of mixing the turbid liquid with the anti-solvent comprises: directly pouring the turbid liquid, slowly dripping it, or controlling the dripping rate by a peristaltic pump to drip into the anti-solvent, or directly pouring the anti-solvent, slowly dripping it, or controlling the dripping rate by a peristaltic pump to drip into the turbid liquid. Preferably, in step 3), the stirring condition is: the stirring temperature is room temperature to 50°C. Preferably, in step 3), the stirring speed is between 100 r / min and 1000 r / min. Preferably, in step 3), the reaction time is 5 to 300 min.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In step 4), the calcination atmosphere is at least one of oxygen, air, nitrogen and argon. Preferably, in step 4), the calcination conditions include: a calcination temperature of 300 to 900° C. and a calcination time of 1 to 10 h.
7. A borate-modified positive electrode material, characterized in that: The borate-modified positive electrode material is prepared by the preparation method according to any one of claims 1 to 6.
8. The positive electrode material according to claim 7, characterized in that The borate-modified positive electrode material is a particle with a core-shell structure. Preferably, the borate-modified positive electrode material comprises a nano-coating shell layer and a coating substrate material, wherein the nano-coating shell layer is modified on the surface of the coating substrate material; and the nano-coating shell layer comprises borate. Preferably, the nano-coating shell layer partially or completely coats the surface of the coating substrate material. Further, the nano-coating shell layer is continuously and evenly distributed on the surface of the coating substrate material.
9. The positive electrode material according to claim 7 or 8, characterized in that: Preferably, the nano-coating shell layer comprises borates of metal elements. Preferably, the thickness of the nano-coating shell layer is 0 nm to 500 nm.
10. Use of the coated positive electrode material according to any one of claims 7 to 9 in energy storage batteries.
Citation Information
Patent Citations
High-nickel cathode material coated with lithium chloroborate and preparation method thereof, and lithium battery
CN110010865A
Cited By
Regeneration method of waste graphite felt electrode of vanadium battery
CN121484108A
A method for regenerating a vanadium cell waste graphite felt electrode
CN121484108B